2018
DOI: 10.18697/ajfand.83.17070
|View full text |Cite
|
Sign up to set email alerts
|

Iron and zinc grain concentrations diversity and agronomic performance of common bean germplasm collected from East Africa

Abstract: Iron and zinc are essential micronutrients for normal human growth and development and are commonly deficient in diets of the most vulnerable. Common bean (Phaseolus vulgaris L.), one of the leading staple foods in East and Central Africa, is a valuable source of quality protein and micronutrients, specifically iron, zinc, and vitamins. Natural variation in micronutrient concentration exists among bean germplasm. Identification of varieties with high iron and zinc seed concentration (FESEED/ZNSEED) for promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(42 reference statements)
1
8
0
2
Order By: Relevance
“…In this research study, we identified some of the bean cultivars containing higher Fe and Zn concentrations from seeds although there were variations in different environments. These data are supported by other similar research conducted in Uganda [24] that showed seed concentration of up to 88 mg/kg and 41mg/kg for Fe and Zn, respectively. Also, in Tanzania, biofortified climbing beans with 80.30 mg/kg Fe [25], India [23], Rwanda and Democratic Republic of Congo with 94 mg/kg Fe [26] were discovered and now are being used by end users.…”
Section: Figure 3: Illustration Of Water Uptake Proportion (I) and Cooking Time (Ii)supporting
confidence: 89%
“…In this research study, we identified some of the bean cultivars containing higher Fe and Zn concentrations from seeds although there were variations in different environments. These data are supported by other similar research conducted in Uganda [24] that showed seed concentration of up to 88 mg/kg and 41mg/kg for Fe and Zn, respectively. Also, in Tanzania, biofortified climbing beans with 80.30 mg/kg Fe [25], India [23], Rwanda and Democratic Republic of Congo with 94 mg/kg Fe [26] were discovered and now are being used by end users.…”
Section: Figure 3: Illustration Of Water Uptake Proportion (I) and Cooking Time (Ii)supporting
confidence: 89%
“…Blair et al (2009) considered a Middle American accession with 42.8 mg kg −1 Zn content on the seeds as a low content and an Andean accession with 66.7 mg kg −1 as high Zn content [57]. Amongi et al (2018) assessed the Zn content of 304 accessions of a common bean germplasm from East Africa. The Zn content on African accessions ranged from 23.9 to 47 mg kg −1 , with an average of 32 mg kg −1 [58].…”
Section: Discussionmentioning
confidence: 99%
“…Amongi et al (2018) assessed the Zn content of 304 accessions of a common bean germplasm from East Africa. The Zn content on African accessions ranged from 23.9 to 47 mg kg −1 , with an average of 32 mg kg −1 [58]. This study obtained a similar range to Blair's, from 42.2 (Posenati) to 59.3 and 59.9 mg Zn kg −1 (Maron and Gialet, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The common bean (Phaseolus vulgaris L.) has considerable potential for biofortification of iron concentration (IC) and zinc concentration (ZC) in the grains because it is the most important pulse crop and leguminous plant for direct human consumption (Beebe et al, 2000) and has relatively high concentrations of these minerals. In addition, various authors have indicated genetic variability in these traits (Amongi et al, 2018;Caproni et al, 2020;Martins et al, 2016;Mukamuhirwa & Rurangwa, 2018;Pereira et al, 2014;Philipo et al, 2020;Silva et al, 2012). In Brazil, most studies have been conducted using precommercial lines.…”
Section: Introductionmentioning
confidence: 99%